Identifikasi dan Karakterisasi Tanaman Kratom melalui Pendekatan Profil Kandungan Senyawa Penanda secara LC-HRMS QToF dan Penetapan Nilai Retention Index secara GCMS - Farida Kurniawati; Dona Fitria; Aan Risma Uli Nainggolan; Puspita Ayu Wardani (Badan Pengawas Obat dan Makanan, 2022)
Kratom is illegally used in traditional medicine and health supplement products. Thus, the analytical method development is needed to identify its presence in final products. Currently, the availability of its markers is limited due to it belongs to restricted substance in Indonesia. The research was conducted to produce alternative analytical method without the use of reference standard. In addition, the research was developed by biomarker profiling approach using mass spectrometer. Mass spectrometry was performed using either gas chromatography or liquid chromatography-high resolution mass spectrometry (LC-HRMS). Both systems were developed to confirm the presence of kratom. A mass spectrometry test was carried out after the marker compounds were extracted from the leaves. The gas chromatography test was carried out using selected ion monitoring (SIM) mode at m/z 214, 397, 383, and 269. The LC-HRMS chromatography system used 0.1 % formic acid as an ion modifier. The analysis was carried out using a quadrupole time of flight (QToF) mass spectrometer as a mass analyzer with electrospray ionization (ESI) in positive mode, running in scan mode analysis. Qualitative analysis was carried out using retention time (Rt) data and ionic fragments of kratom marker compounds. There were three marker compounds obtained, namely speciociliatine, speciogynine, and mitragynine. Specificity test was carried out by identifying their retention time, followed by the determination of their Retention Index (RI) value by GCMS. In addition, m/z value of the marker compounds were confirmed by LC-HRMS QToF. The results showed that three main marker compounds can be used in the identification of kratom adulteration in traditional medicines. This method can be applied as a confirmation test of kratom adulteration in traditional medicine where the LC-HRMS QToF method is more sensitive than GCMS and TLC with LOD values of 149.2 µg/g and 67.6 mg/g respectively after extracted and isolated by TLC.